2001
DOI: 10.2307/3250989
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Virtual Learning Environments: A Research Framework and a Preliminary Assessment of Effectiveness in Basic IT Skills Training

Abstract: Internet technologies are having a significant impact on the learning industry. For-profit organizations and traditional institutions of higher education have developed and are using web-based courses, but little is known about their effectiveness compared to traditional classroom education. Our work focuses on the effectiveness of a webbased virtual learning environment (VLE) in the context of basic information technology skills training. This article provides three main contributions. First, it introduces an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
713
2
49

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,140 publications
(894 citation statements)
references
References 55 publications
(40 reference statements)
40
713
2
49
Order By: Relevance
“…The need to address the competitive demands of globalisation through the adoption of electronic communication and information technology within the workplace has made many organisations embrace virtual team structures (Bal and Teo, 2000;Piccoli et al, 2004;Mogale, 2009). The concept of the virtual team evolved from teleworkers and virtual groups.…”
Section: Concept Of a Virtual Teammentioning
confidence: 99%
See 1 more Smart Citation
“…The need to address the competitive demands of globalisation through the adoption of electronic communication and information technology within the workplace has made many organisations embrace virtual team structures (Bal and Teo, 2000;Piccoli et al, 2004;Mogale, 2009). The concept of the virtual team evolved from teleworkers and virtual groups.…”
Section: Concept Of a Virtual Teammentioning
confidence: 99%
“…A leader's social presence may be difficult to achieve in a virtual environment; thus, creating challenges in team integration, member identification, and coordination (Connaughton and Daly, 2004). It has been argued that the major difference between mediocre and high-performing virtual teams is the development of effective virtual leaders who are able to develop and lead the virtual team to achieve success in project deliverables (Armstrong and Cole, 2002;Piccoli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study concluded that asynchronous e-learning was not effective as a standalone method to deliver technical training for information technology professionals learners in the study commented that e-learning eliminates classroom interaction time, where a significant amount of "real learning" takes place as users assimilate information, utilize software, apply knowledge to problem solving, and interact with the instructor and other learners (Laine, 2003). Other potential problems of e-learning that have been identified in previous research include a sense of learner isolation (Brown, 1996); learner frustration, anxiety, and confusion (Hara & Kling, 2000;Piccoli, Ahmad, & Ives, 2001); higher student attrition rates (Frankola, 2001;Laine, 2003;Ryan, 2001); the need for greater discipline, writing skills, and self-motivation; and the need for online users to make a time commitment to learning (Golladay, Prybutok, & Huff, 2000;Serwatka, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Picoli et al [1] site individual features of trainee such as maturity and ability to work with computer and design/technology features such as reliability of technology and individual interactions have significant effects on e-learning effectiveness. According to the studies of Picoli et al [18], Johnson et al [8] also highlight the importance of interacting and participating educational environment and mention trainees features and technology have influence on e-learning outcomes. Table (1) shows briefly some studies about e-learning CSFs.…”
Section: B E-learning Critical Success Factor (Ecsf)mentioning
confidence: 99%